2020
DOI: 10.1103/physrevlett.124.117401
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Excitation of an Optically Silent Goldstone-Like Phonon Mode

Abstract: It has recently been indicated that the hexagonal manganites exhibit Higgs-and Goldstone-like phonon modes that modulate the amplitude and phase of their primary order parameter. Here, we describe a mechanism by which a silent Goldstone-like phonon mode can be coherently excited, which is based on nonlinear coupling to an infrared-active Higgs-like phonon mode. Using a combination of first-principles calculations and phenomenological modeling, we describe the coupled Higgs-Goldstone dynamics in response to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 83 publications
2
19
0
Order By: Relevance
“…Recent mid-IR pump experiments have observed long-lived metastable ferroelectricity in SrTiO 3 [27] and ferromagnetism in DyFeO 3 [41] and CoF 2 [42], but the precise mechanisms for these phenomena need to be clarified with further experimental studies. Other theoretical predictions based on the nonlinear phonon couplings that await experimental confirmations include indirect-to-direct band gap switching [43], phono-magnetic analogs of opto-magnetic effects [44], cavity control of nonlinear phonon interactions [45], and excitation of an optically silent mode in InMnO 3 [46].…”
Section: Irmentioning
confidence: 99%
“…Recent mid-IR pump experiments have observed long-lived metastable ferroelectricity in SrTiO 3 [27] and ferromagnetism in DyFeO 3 [41] and CoF 2 [42], but the precise mechanisms for these phenomena need to be clarified with further experimental studies. Other theoretical predictions based on the nonlinear phonon couplings that await experimental confirmations include indirect-to-direct band gap switching [43], phono-magnetic analogs of opto-magnetic effects [44], cavity control of nonlinear phonon interactions [45], and excitation of an optically silent mode in InMnO 3 [46].…”
Section: Irmentioning
confidence: 99%
“…In turn, such an IR mode can couple nonlinearly with some Raman modes, provided their irreps satisfy [ΓIR × ΓIR] ⊗ ΓR ⊃ A1g [23]. This mechanism is referred as non-linear phononics [23,45,46], and has allowed experimental [19,[24][25][26][27][28][29][30][46][47][48] and theoretical manipulations of correlated states of matter [49][50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Non-linear Phonon Dynamicsmentioning
confidence: 99%
“…It was also shown that optical pumping with excitation of the electronic subsystem [18][19][20][21] leads only to a temporary decrease in polarization [22][23][24][25]. Following the rapid development and achievements of nonlinear phononics [26][27][28][29], it was proposed to pump the IR-active optical phonon mode, which is nonlinearly coupled with the ferroelectric soft mode [30]. However, in this way, only a transient switching of the polarization was achieved in a monodomain LiNbO 3 sample, followed by the polarization recovery to its initial value on a timescale of about 0.2 ps [31].…”
mentioning
confidence: 99%